COVID-19 in pregnancy: Our experience at a tertiary maternity unit in France - Jessie, Darido; Cynthia, El Haddad; Jed, Diari; Julie, Grevoul Fesquet; Nassima, Bouzid; Andrea, Bobric; Nefissa, Lakhdara; Zeinab, Bazzi; Cindy, Lebis; Louay, Khadam; Luc, Rigonnot (Clinical Journal of Obstetrics and Gynecology, 2020)
Objectives: Our main objectives are to reveal the pregnancy and neonatal impacts of COVID-19 infection and to compare it to the results that are reported in the literature. Methods and materials: The characteristics of the admitted pregnant patients COVID-19 positive with their initial presentation, course at the hospital, and short term follow-up are exposed. Correlation of the age and gestational age with the severity of the disease was calculated. Results: Thirty five COVID-19 positive pregnant patients presented between the beginning of March and the end of April 2020. From 5 weeks till 41 weeks of gestation, all trimesters were included. The mean of age is 32 and the BMI equal 28.2. Associated comorbidities included not only diabetes and hypertension but also PCOS. The symptomatology was considered mild in most of the cases. The distribution of the symptoms included cough in 86%. 10 out of 35 delivered and cesarean was performed in 50% of the cases. The mean length of stay is 6 days. Neither maternal nor neonatal deaths occurred. There is a significant correlation between the age of the patient and the severity of the disease but this is not the case with gestational age. Conclusion: Our results were comparable to the literature in terms of initial presentation, associated comorbidities and the length of stay. Despite the fact that the cesarean rate was high, it was far below that of the literature. More data is still needed about COVID-19 in pregnancy.